The significance of school bullying prevention program: a narrative inquiry from the perspective of a school police officer at a Youth Police Academy in Korea - Hong, Mi Yung; Goo, Jiyeon (Frontiers in Education, 2024)
The need for effective school bullying prevention programs is more pronounced than ever. To address school bullying, Korea has operated the Youth Police Academy (YPA) since 2014. Although the School Police Officers (SPOs) in charge at YPA can provide valuable insights into the significance of school bullying prevention programs, there has been limited research in this area. The purpose of this study is to explore the relevance of school bullying prevention programs and delineate the role of YPA in preventing school bullying, based on the professional experiences and perspectives of YPA’s SPOs. We employed narrative analysis based on interviews with SPOs. The findings revealed that while the majority of SPOs experienced career crises, they overcame these challenges and developed professional perspectives on the YPA program and anti-bullying program. SPOs perceive that school bullying prevention program should focus on ‘resolving relationships,’ ‘collaborative care,’ and ‘teaching coping behaviors.’ Accordingly, YPA can function as a ‘place of reconciliation,’ ‘place helping students understand others’ perspectives through experiential and case-based educational approaches,’ ‘hub for school bullying prevention education grounded in collaboration with relevant institutions and local experts,’ ‘provider of coping information,’ and an ‘active protector of victims.’